A facade or sincere efforts? a case study of political parties' female empowerment agenda in GE 14 - Aminudin, Rabi'ah; Sharif, Megat Muhammad Syamil; Ahmad, Nadzrah (2019)
This study identifies the role of political institution namely political parties in Malaysia that play a crucial role in women's political empowerment. In addition to that, there is a need to analyse Malaysia’s abysmal performance in women's political empowerment which is illustrated in female political representation in political leadership position as well as in legislature and executive organs of government. Malaysia is lagging behind its gender empowerment policies despite the existence of a dedicated ministry to focus on women affairs namely the Ministry of Women, Family, and Community Development established in 2001. Based on the Global Gap Index 2018, Malaysia was ranked at 101st place out of 149 countries which further slips from the 70th out of 144 countries in 2017. This study explores the representation of gender agendas and female candidates in the last General Election in 2018. This paper contributes to understanding the pattern of political parties’ responses towards the demands of female empowerment and inclusion in political processes. It identifies that there has been significant shifts of political parties’ responses towards gender agendas by looking into the electoral manifestos provided by all three coalitions in the last GE 14.